Hédi A. Jaouad. “Limitless Undying Love”: The Ballad of John and Yoko and the Brownings - Sabiston, Elizabeth (Revue CMC Review, 2017)
This review article examines the fascinating link Hédi Abdel Jaouad establishes between popular culture in the Victorian period (Robert and Elizabeth Barrett Browning), and in the postmodern (John and Yoko Lennon).